A Review of BIM Implementation in Indonesia's Smart Cities: Challenges and Opportunities - Maxelino Orlando Lembangan; Esti Asih Nurdiah (Advances in Civil Engineering and Sustainable Architecture, 2025)
Indonesia’s rapid urbanization poses critical challenges to city development and infrastructure management. In response, the government has promoted Smart City initiatives to leverage technology for more sustainable and efficient urban systems. Building Information Modeling (BIM) plays a promising role in supporting these initiatives, particularly in planning, collaboration, and data-driven decision-making. Yet, BIM adoption in Indonesia’s Smart City efforts remains limited due to regulatory, technical, and institutional barriers. This paper reviews current practices, identifies key challenges, and explores opportunities for BIM integration in Indonesian urban development. Through a narrative literature review, the study highlights practical recommendations such as enhancing government-led regulations, capacity building, and cross-sector collaboration. These findings contribute to understanding how BIM can advance Smart City development not only in Indonesia but across similar contexts in the Global South.